A new population of Rosalia longicorn, Rosalia alpina, in Calabria (Southern Italy) (Coleoptera: Cerambycidae) - Terranova, Carlo; Mazzei, Antonio (Fragmenta entomologica, 2023)
The Rosalia longicorn is a species of European Community interest, included in Annexes II and IV of the “Habitats” Directive (Council Directive 92/43/EEC of 21 May 1992 on the conservation of natural habitats and of wild fauna and flora) and is included in the “Red List of Italian saproxylic beetles”. In Calabria (Southern Italy), Rosalia alpina was apparently distributed only in the National Parks. We discuss about the discovery of a new population of Rosalia alpina (Linnaeus, 1758) in a mountainous area of Calabria called Catena Costiera, which is located between two National Parks and constitutes an important wildlife exchange corridor.